(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
The article presents the results of an experiment conducted on meadow-alluvial soils of the Bukhara region, where the groundwater table is at a depth of 2.0–2.5 m. In the experimental cotton field irrigated using drip irrigation, when the pre-irrigation soil moisture was maintained at 75–80–65% of the field capacity (FC), the cotton was irrigated four times according to the 0-4-0 irrigation scheme. No irrigation was applied during the period from germination to flowering, while during the flowering–boll formation stages, four irrigations were carried out with irrigation rates ranging from 616 to 651 m³/ha. The total seasonal irrigation norm amounted to 2521–2537 m³/ha, which is 1594–1633 m³/ha less compared to the control variant, indicating significant water savings